2016
DOI: 10.1002/ece3.2501
|View full text |Cite
|
Sign up to set email alerts
|

Aegean wall lizards switch foraging modes, diet, and morphology in a human‐built environment

Abstract: Foraging mode is a functional trait with cascading impacts on ecological communities. The foraging syndrome hypothesis posits a suite of concurrent traits that vary with foraging mode; however, comparative studies testing this hypothesis are typically interspecific. While foraging modes are often considered typological for a species when predicting foraging‐related traits or mode‐specific cascading impacts, intraspecific mode switching has been documented in some lizards. Mode‐switching lizards provide an oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 77 publications
(129 reference statements)
0
21
0
Order By: Relevance
“…Indeed, individual Aegean wall lizards live and hunt both in their ancestral sandy habitats and in agrarian habitats containing rock walls. Recent work has shown that individuals on rock walls are ambush hunters, jumping from rock to rock, but that individuals in sandy habitats engage in active running pursuit 42 . To facilitate jumping, individuals on rock walls have longer hindlimb-to-forelimb ratios than do their sandy habitat counterparts 42 .…”
Section: Predator–prey Functional Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, individual Aegean wall lizards live and hunt both in their ancestral sandy habitats and in agrarian habitats containing rock walls. Recent work has shown that individuals on rock walls are ambush hunters, jumping from rock to rock, but that individuals in sandy habitats engage in active running pursuit 42 . To facilitate jumping, individuals on rock walls have longer hindlimb-to-forelimb ratios than do their sandy habitat counterparts 42 .…”
Section: Predator–prey Functional Traitsmentioning
confidence: 99%
“…Recent work has shown that individuals on rock walls are ambush hunters, jumping from rock to rock, but that individuals in sandy habitats engage in active running pursuit 42 . To facilitate jumping, individuals on rock walls have longer hindlimb-to-forelimb ratios than do their sandy habitat counterparts 42 . These hunting mode differences lead to dietary differences, where sandy habitat hunters consume more sedentary prey and rock wall hunters consume more mobile prey 42 .…”
Section: Predator–prey Functional Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Podarcis erhardii , the Aegean Wall Lizard, is a common small‐bodied lizard that can be found throughout the Cyclades island group (Aegean Sea, Greece). Adults range in body size between 40 and 75 mm (Valakos et al, 2008) and are largely insectivorous (Adamopoulou, Valakos, & Pafilis, 1999; Donihue, 2016), occasionally bolstering their diet with fruits and conspecific eggs (Brock, Bednekoff, et al, 2014; Brock, Donihue, et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…At one extreme of a continuum, actively roaming/coursing predators typically have large habitat domains; at the other, sit-and-wait/ambush predators usually exhibit smaller domains. Notably, predators may switch hunting modes (Helfman 1990;Olson & Eklov 2005;Donihue 2016), which can change space use, habitat domain size, and contingency in the nature of interactions. Smaller prey may forage locally, whereas larger prey may roam widely depending on their forage requirements in relation to the distribution of plant (or other resource) quality and productivity (Haskell et al .…”
Section: Properties Of the Predatormentioning
confidence: 99%